Conducts of disinfection, pouring and storage of irreversible hydrocolloid impressions by undergraduate students - SILVA,Thalisson Saymo de Oliveira (2016)
Abstract Introduction Obtaining dental models that accurately represent the molded oral tissue requires professional attention, especially when using irreversible hydrocolloid as a molding material. Objective To evaluate the conducts of undergraduate dental students at different internships for the disinfecting procedures, pouring, and storage of irreversible hydrocolloid impressions. Material and method This is an observational, cross-sectional and descriptive study with a census sample of 89 students enrolled in the supervised internships I, II, III and IV. Data collection was performed using a structured questionnaire containing eight questions. Data were analyzed at the 5% significance level. Result Most of the students (88.8%) performed the disinfection procedure, for which the most widely used method (64.6%) was the application of sodium hypochlorite 1% spray stored in a sealed container. The most common disinfection time was 10 minutes (86.1%). Students in the early internships performed better in regard to the proportion of water/plaster to be used compared with students in the final internships. At all internships, pouring and storage of the ensemble of mold and model were neglected during the setting reaction. There was a statistically significant association between the stage and the disinfection method, the ratio of water/powder and pouring of the model (p<0.05). Conclusion Students exhibited appropriate conduct of disinfection; however, they should be encouraged to use evidence-based clinical practices in order to improve the procedures of pouring and storage of irreversible hydrocolloid molds.